Nano-modified polyester fiber super-hydrophobic antistatic material and preparation method thereof

Through the treatment of nanotitanium dioxide, anti-static finishing agent of zinc oxide and superhydrophobic long-chain silane, the problems of hygroscopicity and electrostatic accumulation of polyester fiber fabrics are solved, and the combination of superhydrophobic anti-static properties is achieved, and the wear resistance and durability are improved.

CN120520071APending Publication Date: 2025-08-22SHAANXI COAL & CHEM TECH INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510800883.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-08-22

AI Technical Summary

Technical Problem

Traditional polyester fiber fabrics have poor hygroscopicity, are prone to electrostatic accumulation and dust absorption, and are not durable, which affects aesthetics and service life.

Method used

An antistatic finishing agent of nanotitanium dioxide and zinc oxide and a superhydrophobic finishing solution containing stearyl alcohol, octadecamine and hydrophobic long-chain silane are used to construct a superhydrophobic antistatic polyester fabric through chemical reactions and ultrasonic treatment.

Benefits of technology

The combination of superhydrophobic properties and antistatic ability of polyester fiber fabrics is achieved, maintaining the original excellent performance, and improving wear resistance and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005451212140000011
    Figure HDA0005451212140000011
  • Figure HDA0005451212140000012
    Figure HDA0005451212140000012
Patent Text Reader

Abstract

The invention belongs to the technical field of textile materials, and discloses a nano-modified polyester fiber super-hydrophobic antistatic material and a preparation method thereof.The preparation method comprises the steps that fabric is soaked in an antistatic finishing agent containing nano titanium dioxide and zinc oxide and then dried, then soaked in super-hydrophobic finishing liquid containing stearyl alcohol, octadecylamine and hydrophobic long-chain silane, dried and dried, and the nano-modified polyester fiber super-hydrophobic antistatic material is obtained. And drying to obtain the super-hydrophobic antistatic polyester fiber fabric. According to the invention, an antistatic finishing agent containing nano zinc oxide and a super-hydrophobic finishing liquid containing octadecylamine and hydrophobic long-chain silicon are utilized, so that the excellent conductivity of metal oxide nano titanium dioxide / zinc oxide and a hydrophobic structure constructed by stearyl alcohol, octadecylamine and low-surface-energy substances on the surface of the material are ingeniously fused; therefore, the polyester fiber fabric is endowed with outstanding super-hydrophobic characteristics and excellent antistatic capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of textile materials, and in particular to a nano-modified polyester fiber super-hydrophobic antistatic material and a preparation method thereof. Background Art

[0002] Polyester fabrics are widely used in clothing, home furnishings, and industrial applications due to their excellent abrasion resistance, wrinkle resistance, and dyeability. However, traditional polyester fabrics have low hygroscopicity, poor electrical conductivity, and a high coefficient of friction, which leads to a high accumulation of static electricity. This makes the surface susceptible to dust, which not only affects the appearance of clothing but also reduces the efficiency and service life of equipment.

[0003] Superhydrophobic materials, with their unique repellency to liquid water and low adhesion, have shown remarkable application prospects in a variety of fields, including corrosion protection, antifreeze, self-cleaning, oil-water separation, and biomedicine. In recent years, significant progress has been made in research and industrialization in this field. Through sophisticated surface micro- and nanostructure design and modification of low-surface-energy materials, superhydrophobic coatings and materials with excellent performance and strong stability have been successfully developed. However, the application of superhydrophobic materials faces challenges such as the need for enhanced durability and complex processing.

[0004] Therefore, it is very important to develop superhydrophobic materials that have good wear resistance, simple processing, good durability, and polyester fiber composite materials that also have antistatic properties. Summary of the Invention

[0005] In order to solve the problem that polyester fabrics have insufficient hygroscopicity, are prone to static electricity accumulation and dust adsorption, and have poor durability, the purpose of the present invention is to provide a nano-modified polyester fiber super-hydrophobic antistatic material and a preparation method.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a super-hydrophobic antistatic polyester fiber fabric comprises the following steps:

[0008] The fabric is impregnated with an antistatic finishing agent containing nano-titanium dioxide and zinc oxide and then dried, and then impregnated with a super-hydrophobic finishing liquid containing stearyl alcohol, octadecylamine and hydrophobic long-chain silane, and then dried to obtain a super-hydrophobic antistatic polyester fiber fabric.

[0009] Furthermore, the antistatic finishing agent containing nano titanium dioxide and zinc oxide is prepared by the following process:

[0010] Adding nano zinc oxide to an aqueous solution containing glacial acetic acid and stirring evenly to obtain a nano zinc oxide suspension;

[0011] Dissolve tetrabutyl titanate in glacial acetic acid and stir evenly to obtain tetrabutyl titanate acetic acid solution;

[0012] Tetrabutyl titanate acetic acid solution and nano zinc oxide suspension are reacted at 40-50° C. for 1-3 hours, and then polyvinyl pyrrolidone is added to obtain an antistatic finishing agent containing nano titanium dioxide and zinc oxide.

[0013] Furthermore, the pH value of the aqueous solution containing glacial acetic acid is 2, and the dosage ratio of nano-zinc oxide to the aqueous solution containing glacial acetic acid in the nano-zinc oxide suspension is 1-3 g: 10-30 mL;

[0014] The volume ratio of tetrabutyl titanate to glacial acetic acid in the tetrabutyl titanate acetic acid solution is 4.2-12:15-45;

[0015] The usage ratio of nano zinc oxide and tetrabutyl titanate is 1-3 g:4.2-12 mL.

[0016] Furthermore, the amount of polyvinyl pyrrolidone used is 3-7 wt% of the mass of the antistatic finishing agent.

[0017] Furthermore, a super-hydrophobic finishing liquid containing stearyl alcohol, octadecylamine and hydrophobic long-chain silane is prepared by the following process:

[0018] Dissolve stearyl alcohol and octadecylamine in an organic solvent, mix them evenly, then add hydrophobic long-chain silane, mix them evenly, and obtain a super-hydrophobic finishing liquid containing stearyl alcohol and octadecylamine.

[0019] Furthermore, the organic solvent is one or more of anhydrous ethanol, methanol, isopropanol, acetone and ethyl acetate.

[0020] Furthermore, the hydrophobic long-chain silane is one or more of polydimethylsiloxane, alkyltrichlorosilane, alkyltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane and propyltriethoxysilane.

[0021] Furthermore, the mass ratio of stearyl alcohol, octadecylamine and hydrophobic long-chain silane is 0.5-0.6:0.6-0.7:0.1-0.4.

[0022] Furthermore, the mass ratio of stearyl alcohol to the organic solvent is 0.5-0.6:50-100.

[0023] A super-hydrophobic and antistatic polyester fiber fabric.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention utilizes an antistatic finishing agent containing nano-titanium dioxide and zinc oxide, and a super-hydrophobic finishing liquid containing octadecylamine and hydrophobic long-chain silicon. This cleverly combines the excellent conductive properties of the metal oxide nano-titanium dioxide / zinc oxide with the hydrophobic structure constructed on the material surface using stearyl alcohol, octadecylamine, and a low-surface-energy hydrophobic long-chain silane. This results in polyester fiber fabrics possessing excellent super-hydrophobic properties and antistatic capabilities while maintaining the inherent excellent properties of the polyester fiber. The present invention provides a new super-hydrophobic antistatic fabric preparation technology for the textile industry, with broad application prospects.

[0026] Furthermore, during the preparation of superhydrophobic finishing liquid, the amount of raw materials used and the ultrasonic treatment time both affect the hydrophobic effect of the finishing liquid, because the construction of a superhydrophobic surface requires two conditions, namely, the material surface needs to have a micro-nano structure and needs to be modified with a low surface energy hydrophobic long-chain silane. These structures require fine control. If the mixing is uneven, it will lead to poor hydrophobic effect.

[0027] Furthermore, during the preparation of the antistatic finishing liquid, the amount of raw materials, temperature, and time will affect the performance of the antistatic agent, because this process involves a chemical reaction. If the reaction temperature is too low, the amount of titanium dioxide generated will be small, thus affecting the antistatic effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the preparation of the super-hydrophobic and antistatic polyester fabric of the present invention;

[0029] Figure 2 Schematic diagram of the hydrophobic mechanism of superhydrophobic surface micro-nanostructure.

[0030] Figure symbols: A-polyester fabric, B-antistatic finishing agent, C-superhydrophobic finishing liquid, D-superhydrophobic antistatic polyester composite material; (1) indicates that the polyester fabric is immersed in the antistatic finishing agent, and (2) indicates that the fabric, which has been immersed in the antistatic finishing agent and then treated and dried, is immersed in the superhydrophobic finishing liquid again. DETAILED DESCRIPTION

[0031] To facilitate understanding of the present invention, the present invention will be described more fully below with reference to the accompanying drawings. The accompanying drawings illustrate preferred embodiments of the present invention. However, the present invention may be implemented in a variety of different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and comprehensive understanding of the disclosure of the present invention.

[0032] See also Figure 1 The preparation method of the super-hydrophobic antistatic polyester fiber fabric of the present invention comprises the following steps:

[0033] 1. Preparation of superhydrophobic finishing liquid:

[0034] Stearyl alcohol and octadecylamine were dissolved in an organic solvent, magnetically stirred for 2 hours, and then ultrasonically dispersed for 30 minutes to obtain a uniform solution. Subsequently, a hydrophobic long-chain silane was added to the solution under continuous stirring and ultrasonicated for another 30 minutes to obtain a uniform superhydrophobic finishing solution C.

[0035] The organic solvent is one or more of anhydrous ethanol, methanol, isopropanol, acetone and ethyl acetate.

[0036] The hydrophobic long-chain silane is one or more of polydimethylsiloxane, alkyltrichlorosilane, alkyltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane and propyltriethoxysilane.

[0037] The usage ratio of stearyl alcohol, octadecylamine, hydrophobic long-chain silane and organic solvent is 0.5-0.6 g: 0.6-0.7 g: 0.1-0.4 g: 50-100 mL.

[0038] 2. Preparation of antistatic finishing agent:

[0039] Add a certain amount of nano zinc oxide to an aqueous solution containing glacial acetic acid (pH=2) and stir evenly at room temperature to obtain a nano zinc oxide suspension; the dosage ratio of nano zinc oxide to glacial acetic acid (pH=2) is 1-3 g: 10-30 mL;

[0040] A certain amount of tetrabutyl titanate is dissolved in glacial acetic acid and stirred evenly to obtain a tetrabutyl titanate acetic acid solution; the dosage ratio of tetrabutyl titanate to glacial acetic acid is 4.2-12 mL:15-45 mL.

[0041] Slowly add the tetrabutyl titanate acetate solution to the nano zinc oxide suspension. After the addition is complete, stir for 30 minutes, then heat to 40-50°C and react for 1-3 hours. Then add a certain amount of polyvinyl pyrrolidone to obtain antistatic finishing agent B, namely a titanium dioxide / zinc oxide composite solution.

[0042] The dosage ratio of nano zinc oxide to tetrabutyl titanate is 1-3 g: 4.2-12 mL;

[0043] The amount of polyvinyl pyrrolidone used is 3-7wt% of the total weight of the antistatic finishing agent.

[0044] 3. A 3 cm*3 cm polyester fabric (i.e., polyester fabric A) was ultrasonically cleaned in deionized water and anhydrous ethanol for 15 min respectively to remove impurities and grease on the fabric surface, and then vacuum dried at 80-100°C.

[0045] 4. Take the dried polyester fabric and soak it in the titanium dioxide / zinc oxide composite solution. Place the sample in a vacuum constant temperature environment at 80-100℃ and dry it.

[0046] 5. The fabric obtained in step 4 is soaked in the super-hydrophobic finishing liquid obtained in step 1 for 1-3 minutes, and the sample is placed in a vacuum constant temperature drying at 80-100° C. for 0.5-1 hour to obtain a super-hydrophobic antistatic polyester composite material D.

[0047] See also Figure 2 The super-hydrophobic surface of the nano-modified polyester fiber super-hydrophobic antistatic material of the present invention has a micro-nano structure. The hydrophobic mechanism of the micro-nano structure is as follows: stearyl alcohol and octadecylamine molecules precipitate to form micron / nanoscale hydrophobic protrusions, increasing the surface roughness; hydrophobic long-chain silane forms a hydrophobic base (solid) after film formation; air is retained in the microscopic grooves (aircushion), and the droplets exhibit a Cassie-Baxter state (contact angle >150°, rolling angle <10°).

[0048] The following are specific examples.

[0049] Example 1

[0050] 1. Preparation of superhydrophobic finishing liquid:

[0051] 0.5g of commercially available stearyl alcohol and 0.6g of octadecylamine were dissolved in 50ml of anhydrous ethanol, magnetically stirred for 2 hours, and then ultrasonically dispersed for 30 minutes to obtain a uniform solution. Subsequently, 0.3g of polydimethylsiloxane was added to the solution while stirring continuously, and ultrasonication was continued for 30 minutes to obtain a uniform superhydrophobic finishing solution.

[0052] 2. Preparation of antistatic finishing agent:

[0053] 1.0 g of nano zinc oxide was added to a solution containing 10 mL of glacial acetic acid (pH = 2), and stirred and ultrasonicated at room temperature to obtain a nano zinc oxide suspension;

[0054] Dissolve 4.2 mL of tetrabutyl titanate in 15 mL of glacial acetic acid and stir evenly to obtain a tetrabutyl titanate acetic acid solution;

[0055] The tetrabutyl titanate acetate solution was slowly added dropwise to the nano zinc oxide suspension. After the addition was complete, the mixture was stirred for 30 minutes and then heated to 45°C for 2 hours. Then, 0.70 g of polyvinyl pyrrolidone was added to obtain an antistatic finishing agent, namely a titanium dioxide / zinc oxide composite solution.

[0056] 3. Ultrasonic cleaning of 3cm*3cm polyester fabric in 20mL deionized water and 20mL anhydrous ethanol for 15min respectively to remove impurities and grease on the surface of the fabric, and then vacuum drying at 80-100℃.

[0057] 4. Take the dried polyester fabric and soak it in the titanium dioxide / zinc oxide composite solution. Place the sample in a vacuum constant temperature environment at 80-100℃ and dry it.

[0058] 5. The contact angle of the fabric surface after two immersion treatments was measured using a contact angle meter. The contact angle of water was 152° and the voltage half-life of the fabric after treatment was 2s.

[0059] Example 2

[0060] 1. Preparation of superhydrophobic finishing liquid:

[0061] Dissolve 0.5g of stearyl alcohol and 0.6g of octadecylamine in 50ml of methanol, magnetically stir for 2h, and then ultrasonically disperse for 30min to obtain a homogeneous solution. Subsequently, add 0.1g of vinyltrimethoxysilane and 0.2g of propyltriethoxysilane to the solution while stirring continuously, and continue ultrasonicating for 30min to obtain a uniform superhydrophobic finishing solution.

[0062] 2. Preparation of antistatic finishing agent:

[0063] 3.0 g of nano zinc oxide was added to a solution containing 30 mL of glacial acetic acid (pH = 2), and stirred and ultrasonicated at room temperature to obtain a nano zinc oxide suspension;

[0064] Dissolve 12 mL of tetrabutyl titanate in 35 mL of glacial acetic acid and stir evenly to obtain a tetrabutyl titanate acetic acid solution;

[0065] Slowly add the tetrabutyl titanate acetate solution dropwise to the nano-zinc oxide suspension. After complete addition, stir for 30 minutes, then heat to 40°C and react for 3 hours. Then, add polyvinyl pyrrolidone to obtain an antistatic finish, namely a titanium dioxide / zinc oxide composite solution. The weight of polyvinyl pyrrolidone should be 3 wt% of the total weight of the antistatic finish.

[0066] 3. Ultrasonic cleaning of 3cm*3cm polyester fabric in 20mL deionized water and 20mL anhydrous ethanol for 15min respectively to remove impurities and grease on the surface of the fabric, and then vacuum drying at 80-100℃.

[0067] 4. Take the dried polyester fabric and soak it in the titanium dioxide / zinc oxide composite solution. Place the sample in a vacuum constant temperature environment at 80-100℃ and dry it.

[0068] 5. The contact angle of the fabric surface after two immersion treatments was measured using a contact angle meter. The contact angle of water was 153° and the voltage half-life of the fabric after treatment was 1s.

[0069] Example 3

[0070] 1. Preparation of superhydrophobic finishing liquid:

[0071] Dissolve 0.6g of stearyl alcohol and 0.65g of octadecylamine in 100ml of isopropyl alcohol, magnetically stir for 2 hours, and then ultrasonically disperse for 30 minutes to obtain a uniform solution. Subsequently, add 0.4g of methyltriethoxysilane to the solution while stirring continuously, and continue ultrasonicating for 30 minutes to obtain a uniform superhydrophobic finishing solution.

[0072] 2. Preparation of antistatic finishing agent:

[0073] 2.0 g of nano zinc oxide was added to a solution containing 15 mL of glacial acetic acid (pH = 2), and the solution was stirred and ultrasonicated at room temperature to obtain a nano zinc oxide suspension;

[0074] Dissolve 5 mL of tetrabutyl titanate in 30 mL of glacial acetic acid and stir evenly to obtain a tetrabutyl titanate acetic acid solution;

[0075] Slowly add the tetrabutyl titanate acetate solution dropwise to the nano-zinc oxide suspension. After complete addition, stir for 30 minutes, then heat to 50°C and react for 1 hour. Then, add polyvinyl pyrrolidone to obtain an antistatic finish, namely a titanium dioxide / zinc oxide composite solution. The weight of polyvinyl pyrrolidone should be 7 wt% of the total weight of the antistatic finish.

[0076] 5. The contact angle of the fabric surface after two immersion treatments was measured using a contact angle meter. The contact angle of water was 150° and the voltage half-life of the fabric after treatment was 2s.

[0077] Example 4

[0078] 1. Preparation of superhydrophobic finishing liquid:

[0079] Dissolve 0.55g of stearyl alcohol and 0.7g of octadecylamine in 70ml of acetone, stir magnetically for 2 hours, and then ultrasonically disperse for 30 minutes to obtain a uniform solution. Subsequently, add 0.2g of methyltrimethoxysilane to the solution while stirring continuously, and continue ultrasonicating for 30 minutes to obtain a uniform superhydrophobic finishing solution.

[0080] 2. Preparation of antistatic finishing agent:

[0081] 1.0 g of nano zinc oxide was added to a solution containing 20 mL of glacial acetic acid (pH = 2), and the solution was stirred and ultrasonicated at room temperature to obtain a nano zinc oxide suspension;

[0082] Dissolve 8 mL of tetrabutyl titanate in 25 mL of glacial acetic acid and stir evenly to obtain a tetrabutyl titanate acetic acid solution;

[0083] Slowly add the tetrabutyl titanate acetate solution dropwise to the nano-zinc oxide suspension. After complete addition, stir for 30 minutes, then heat to 45°C and react for 2 hours. Then, add polyvinyl pyrrolidone to obtain an antistatic finish, namely a titanium dioxide / zinc oxide composite solution. The weight of polyvinyl pyrrolidone should be 5 wt% of the total weight of the antistatic finish.

[0084] 3. Ultrasonic cleaning of 3cm*3cm polyester fabric in 20mL deionized water and 20mL anhydrous ethanol for 15min respectively to remove impurities and grease on the surface of the fabric, and then vacuum drying at 80-100℃.

[0085] 4. Take the dried polyester fabric and soak it in the titanium dioxide / zinc oxide composite solution. Place the sample in a vacuum constant temperature environment at 80-100℃ and dry it.

[0086] 5. The contact angle of the fabric surface after two immersion treatments was measured using a contact angle meter. The contact angle of water was 153° and the voltage half-life of the fabric after treatment was 2s.

[0087] Example 5

[0088] 1. Preparation of superhydrophobic finishing liquid:

[0089] 0.52g of commercially available stearyl alcohol and 0.68g of octadecylamine were dissolved in 80ml of ethyl acetate, magnetically stirred for 2 hours, and then ultrasonically dispersed for 30 minutes to obtain a homogeneous solution. Subsequently, 0.3g of alkyltrimethoxysilane was added to the solution while stirring continuously, and ultrasonication was continued for 30 minutes to obtain a uniform superhydrophobic finishing solution.

[0090] 2. Preparation of antistatic finishing agent:

[0091] 1.0 g of nano zinc oxide was added to a solution containing 25 mL of glacial acetic acid (pH = 2), and the solution was stirred and ultrasonicated at room temperature to obtain a nano zinc oxide suspension;

[0092] Dissolve 10 mL of tetrabutyl titanate in 20 mL of glacial acetic acid and stir evenly to obtain a tetrabutyl titanate acetic acid solution;

[0093] Slowly add the tetrabutyl titanate acetate solution dropwise to the nano-zinc oxide suspension. After complete addition, stir for 30 minutes, then heat to 42°C and react for 2 hours. Then, add polyvinyl pyrrolidone to obtain an antistatic finish, namely a titanium dioxide / zinc oxide composite solution. The weight of polyvinyl pyrrolidone should be 4 wt% of the total weight of the antistatic finish.

[0094] 3. Ultrasonic cleaning of 3cm*3cm polyester fabric in 20mL deionized water and 20mL anhydrous ethanol for 15min respectively to remove impurities and grease on the surface of the fabric, and then vacuum drying at 80-100℃.

[0095] 4. Take the dried polyester fabric and soak it in the titanium dioxide / zinc oxide composite solution. Place the sample in a vacuum constant temperature environment at 80-100℃ and dry it.

[0096] 5. The contact angle of the fabric surface after two immersion treatments was measured using a contact angle meter. The contact angle of water was 152° and the voltage half-life of the fabric after treatment was 2s.

[0097] Example 6

[0098] 1. Preparation of superhydrophobic finishing liquid:

[0099] 0.6g of commercially available stearyl alcohol and 0.63g of octadecylamine were dissolved in a mixture of 30ml of anhydrous ethanol and 30ml of methanol. The mixture was magnetically stirred for 2 hours and then ultrasonically dispersed for 30 minutes to obtain a homogeneous solution. Subsequently, 0.25g of alkyltrichlorosilane was added to the solution while stirring continuously, and ultrasonication was continued for 30 minutes to obtain a uniform superhydrophobic finishing solution.

[0100] 2. Preparation of antistatic finishing agent:

[0101] 1.0 g of nano zinc oxide was added to a solution containing 10 mL of glacial acetic acid (pH = 2), and stirred and ultrasonicated at room temperature to obtain a nano zinc oxide suspension;

[0102] Dissolve 4.2 mL of tetrabutyl titanate in 15 mL of glacial acetic acid and stir evenly to obtain a tetrabutyl titanate acetic acid solution;

[0103] Slowly add the tetrabutyl titanate acetate solution dropwise to the nano-zinc oxide suspension. After complete addition, stir for 30 minutes, then heat to 47°C and react for 1.5 hours. Then, add polyvinyl pyrrolidone to obtain an antistatic finish, namely a titanium dioxide / zinc oxide composite solution. The weight of polyvinyl pyrrolidone should be 6 wt% of the total weight of the antistatic finish.

[0104] 3. Ultrasonic cleaning of 3cm*3cm polyester fabric in 20mL deionized water and 20mL anhydrous ethanol for 15min respectively to remove impurities and grease on the surface of the fabric, and then vacuum drying at 80-100℃.

[0105] 4. Take the dried polyester fabric and soak it in the titanium dioxide / zinc oxide composite solution. Place the sample in a vacuum constant temperature environment at 80-100℃ and dry it.

[0106] 5. The contact angle of the fabric surface after two immersion treatments was measured using a contact angle meter. The contact angle of water was 154° and the voltage half-life of the fabric after treatment was 2s.

[0107] Comparative Example 1

[0108] 1) Ultrasonic cleaning of 3 cm x 3 cm polyester fabric in 20 mL of deionized water and 20 mL of anhydrous ethanol for 15 min respectively to remove impurities and grease on the fabric surface, and then vacuum drying at 80-100°C.

[0109] 2) The contact angle of the cleaned fabric surface was measured using a contact angle meter. The water contact angle was 85°. The voltage half-life of the untreated fabric was 22 seconds.

[0110] By comparing Example 1 with Comparative Example 1, it can be seen that the superhydrophobicity and antistatic properties of the fabric of the present invention are improved by being treated with the superhydrophobic finishing liquid and the antistatic finishing agent.

[0111] The polyester composite material prepared by the present invention has good durability, is easy to prepare and has self-cleaning performance.

[0112] The above description is merely a description of the preferred embodiment of the present invention and is not to be construed as limiting the claims. The present invention is not limited to the above embodiment, and variations in the specific structure are permitted. Any variations made within the scope of the independent claims of the present invention are also within the scope of protection of the present invention.

[0113] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention pertains. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

Claims

1. A method for preparing a super-hydrophobic antistatic polyester fiber fabric, characterized in that: The following steps are involved: The fabric is impregnated with an antistatic finishing agent containing nano-titanium dioxide and zinc oxide and then dried, and then impregnated with a super-hydrophobic finishing liquid containing stearyl alcohol, octadecylamine and hydrophobic long-chain silane, and then dried to obtain a super-hydrophobic antistatic polyester fiber fabric.

2. The method for preparing a super-hydrophobic antistatic polyester fiber fabric according to claim 1, wherein: The antistatic finishing agent containing nano titanium dioxide and zinc oxide is prepared by the following process: Adding nano zinc oxide to an aqueous solution containing glacial acetic acid and stirring evenly to obtain a nano zinc oxide suspension; Dissolve tetrabutyl titanate in glacial acetic acid and stir evenly to obtain tetrabutyl titanate acetic acid solution; Tetrabutyl titanate acetic acid solution and nano zinc oxide suspension are reacted at 40-50° C. for 1-3 hours, and then polyvinyl pyrrolidone is added to obtain an antistatic finishing agent containing nano titanium dioxide and zinc oxide.

3. The method for preparing the super-hydrophobic antistatic polyester fiber fabric according to claim 1, wherein: The pH value of the aqueous solution containing glacial acetic acid is 2, and the dosage ratio of nano-zinc oxide to the aqueous solution containing glacial acetic acid in the nano-zinc oxide suspension is 1-3 g: 10-30 mL; The volume ratio of tetrabutyl titanate to glacial acetic acid in the tetrabutyl titanate acetic acid solution is 4.2-12:15-45; The usage ratio of nano zinc oxide and tetrabutyl titanate is 1-3 g:4.2-12 mL.

4. The method for preparing a super-hydrophobic antistatic polyester fiber fabric according to claim 1, wherein: The amount of polyvinyl pyrrolidone used is 3-7wt% of the mass of the antistatic finishing agent.

5. The method for preparing the super-hydrophobic antistatic polyester fiber fabric according to claim 1, wherein: The super-hydrophobic finishing liquid containing stearyl alcohol, octadecylamine and hydrophobic long-chain silane is prepared by the following process: Dissolve stearyl alcohol and octadecylamine in an organic solvent, mix them evenly, then add hydrophobic long-chain silane, mix them evenly, and obtain a super-hydrophobic finishing liquid containing stearyl alcohol and octadecylamine.

6. The method for preparing the super-hydrophobic antistatic polyester fiber fabric according to claim 5, characterized in that: The organic solvent is one or more of anhydrous ethanol, methanol, isopropanol, acetone and ethyl acetate.

7. The method for preparing the super-hydrophobic antistatic polyester fiber fabric according to claim 5, characterized in that: The hydrophobic long-chain silane is one or more of polydimethylsiloxane, alkyltrichlorosilane, alkyltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane and propyltriethoxysilane.

8. The method for preparing the super-hydrophobic antistatic polyester fiber fabric according to claim 5, characterized in that: The mass ratio of stearyl alcohol, octadecylamine and hydrophobic long-chain silane is 0.5-0.6:0.6-0.7:0.1-0.

4.

9. The method for preparing the super-hydrophobic antistatic polyester fiber fabric according to claim 5, wherein: The mass ratio of stearyl alcohol to the organic solvent is 0.5-0.6:50-100.

10. A super-hydrophobic antistatic polyester fiber fabric prepared according to the method according to any one of claims 1 to 9.